Dengue vaccine endgame: why has the global response to exponential demand in the tropics been so slow? - Possas, Cristina; Marques, Ernesto T. A.; Oliveira, Alessandra; Schumacher, Suzanne; Antunes, Adelaide; Homma, Akira (Frontiers in Tropical Diseases, 2024)
IntroductionThere has been a dramatic global surge in dengue fever (DF) in recent years, with a projected 100-400 million cases annually and large outbreaks expected every 3-4 years. This concerning scenario is in sharp contrast to the very low availability of dengue vaccines to meet this spiraling demand, particularly affecting developing countries in Latin America and Africa. In our study, we aim to identify current vaccine development constraints, from a technological perspective, based on clinical trials and patent landscape data.MethodsThis study was conducted in a two-step methodology. First, candidates and launched products and methods used in the development or as part of DF vaccines were identified from the Cortellis Drug Discovery Intelligence (CDDI) platform. Second, the Derwent Innovation database was used to retrieve patent documents related to dengue vaccines. Data were collected in the period 2014-2024 (to identify the candidate and or launched vaccines) and 2018-2022 (to identify patent documents) with claims involving applications for dengue vaccine development. We presented these descriptive data in the following format: quantitative and qualitative assessments describing the vaccine development scenario and the claimed vaccine technologies.ResultsOur study indicated that 65% of dengue vaccines are still in phase 1 of development. The few current dengue vaccines that have reached phase 3 (1) and launched (2) have shown limited levels of individual protection for one or more dengue serotypes and there is an anemic pipeline of the next generation of more effective tetravalent dengue vaccines. Although the intelligent use of multiple dengue vaccine formulations in immunization campaigns can result in effective protection against all serotypes at the population level, the implementation of this is complex and challenging. The results of our study thus provide evidence of a worrisome global situation regarding the development of new dengue vaccine candidates.ConclusionTo reverse this scenario, there is an urgent need to implement new knowledge governance approaches and business models to stimulate an exponential increase in global vaccine development funding for dengue and several other vaccines.